Toward Engineered Nanoparticle-Doped Optical Fibers for Sensor Applications - Lu, Zhuorui; Robine , Thibaut; Molardi, Carlo; Pigeonneau, Franck; Tosi, Daniele; Blanc, Wilfried (Frontiers in Sensors, 2022)
Nanoparticle-doped optical fibers, investigated first as fiber lasers and fiber amplifiers, have gained tremendous interest over the past few years as fiber sensors. One of the main interests of such fibers relies on the ability to develop a distributed sensor, allowing real-time measurement with multiplexed architecture. To go beyond the actual proof of concept, we discuss in this perspective paper three main challenges to tackle: understanding light propagation in heterogeneous materials, controlling nanoparticle formation in glass, and engineering nanoparticle characteristics. Identified as the main directions to follow, they will contribute to promote nanoparticle-doped fiber sensors in the next few years.